The Influence of Tahfiz Education on the Human Soul according to Al-Ghazali's Perspective - Mohd Solahuddin Shahruddin; Mohd Yadman Sarwan; Muhammad Syukri Mohd Ashmir Wong; Nasharuddin Mohammad; Muhammad Zuhaili Saiman; S Salahudin Suyurno (Universiti Sains Islam Malaysia, 2025)
Journal of Quran Sunnah Education & Special Needs, Volume 8 Issue 2 Page (104-112)